Gambaran Frekuensi Menyikat Gigi dan Jenis Bulu Sikat Gigi dengan Karies Gigi pada Siswa Sekolah Dasar Negeri 042 Gambir Bandung - Muhammad Faisal Akhdaan Dzaki; Yuniarti; Meta Maulida Damayanti (UNISBA Press, 2024)
Abstract. As much as 45.3% of Indonesia's population suffers from dental caries, and in Bandung City as much as 47.88% of the population of Bandung City suffers from dental caries. Dental caries is a process of demineralization of hard tooth tissue with multi-factorial etiology. This study aims to determine the description of toothbrush frequency and type of toothbrush bristles with the incidence of dental caries in students at SDN Gambir 042 Bandung. The subject sampling technique used consecutive sampling with 82 research subjects. This research uses an analytical observational method with a cross-sectional approach. Data collection was carried out by examining the teeth of the research subjects. The results of this study showed that the frequency of toothbrushing for students at SDN Gambir 042 two or more times a day was 69 students (84.1%) and once a day 13 students (15.9%). Then for the types of brush bristles used by students, there were 52 students (63.4%) with soft bristle brushes, 27 students (32.9%) with medium bristle brushes, and 3 students (3.7%) with coarse bristle brushes. And the incidence of dental caries among students was 71 students with caries (86.6%) and 11 students without caries (13.4%). Likewise, the relationship between the type of toothbrush bristle and the incidence of caries was not significant. The frequency of brushing your teeth and choosing the correct type of toothbrush bristles are not absolute factors in preventing dental caries because there are other factors in brushing your teeth such as duration, time and technique. Apart from that, there are also other factors outside of brushing teeth, such as the person's age, diet and saliva levels. Abstrak. Sebanyak 45,3% populasi Indonesia menderita karies gigi, dan di Kota Bandung sebanyak 47,88% dari populasi Kota Bandung menderita karies gigi. Karies gigi adalah proses demineralisasi jaringan keras gigi dari etiologi yang multi faktorial. Penelitian ini bertujuan untuk mengetahui gambaran frekuensi sikat gigi dan jenis bulu sikat gigi dengan kejadian karies gigi pada siswa SDN Gambir 042 Bandung. Teknik pengambilan subjek menggunakan consecutive sampling dengan subjek penelitian sebanyak 82 orang. Penelitian ini menggunakan metode observasional analitik dengan pendekatan potong lintang. Pengambilan data dilakukan dengan memeriksa gigi dari subjek penelitian. Hasil penelitian ini menunjukkan frekuensi sikat gigi siswa SDN Gambir 042 dengan dua atau lebih dari dua kali sehari adalah 69 siswa (84,1%) dan satu kali sehari 13 siswa (15,9%). Lalu untuk jenis bulu sikat yang digunakan oleh siswa dengan bulu sikat halus berjumlah 52 siswa (63,4%), bulu sikat sedang 27 siswa (32,9%), dan bulu sikat kasar 3 siswa (3,7%). Dan kejadian karies gigi pada siswa terdapat 71 siswa karies (86,6%) dan 11 siswa tidak terdapat karies (13,4%). demikian pula hubungan jenis bulu sikat gigi dengan kejadian karies didapatkan hasil yang tidak signifikan. Frekuensi menyikat gigi dan pemilihan jenis bulu sikat gigi yang benar tidak menjadi faktor mutlak untuk mencegah karies gigi karena terdapat faktor lain dari menyikat gigi seperti durasi, waktu, dan teknik. Selain itu, terdapat juga faktor lain di luar menyikat gigi, seperti usia, diet, dan kadar saliva orang tersebut.